PTSD in French Adolescent Victims Following the London Attack in March 2017: Data From the First Step of the AVAL Study - Coulon, Nathalie; Grenon, Marion; Consigny, Maëlys; Simson, J-P (Frontiers in Psychiatry, 2022)
Background The terrorist attack at Westminster Bridge on March 22nd, 2017 impacted on French high school students on a school trip in London. This terrorist attack was claimed by the Islamic State. The aim of the study was to assess the mental health consequences of the attack on the French adolescents who were directly exposed (criteria A for Post-Traumatic Stress Disorder, PTSD). This involved three dimensions, namely: (1) clinical; (2) epidemiological; and (3) prevention and therapeutic. Material and Method The investigation was the first observational step of AVAL (Adolescents Victimes de l'Attentat de Londres) study, a cohort monitoring project and it was then a monocentric, cross sectional, non interventional survey, at only one-year post-trauma. The study was carried out utilizing self- and clinician-administered questionnaires. Volunteers from the medico-psychological emergency unit provided support for these victims during the study protocol. Results From the target population (n = 53), 39 adolescents (73.6%) agreed to participate, with a median age 16.9 years. 12 months after the attack, 25.6% of teenagers suffered from current PTSD (p < 0.0001). Those with, vs. without, PTSD showed several significant differences: (1) heightened levels of major depressive episodes (p = 0.0266) and suicidality (p = 0.0164); (2) increased substance use, including tobacco (p = 0.0284) and cannabis (p = 0.0449); and (3) impaired functioning in school (p = 0.0203), social (p < 0.0001) and family (p < 0.0001) settings. Sixty four percentage of directly exposed teenagers also had a current psychiatric disorder other than PTSD. Discussion The heightened levels of PTSD, psychiatric disorders, and substance use at 12 months highlight the importance of early intervention in adolescents exposed to terrorist-linked potentially traumatic events.